LOGIC, MYSTERY, AND HUMANITY: AN ANALYSIS OF SIR ARTHUR CONAN DOYLE'S SHERLOCK HOLMES - Visola Hamidova; Shavkatov Sherzod Shavkatovich (TADQIQOTLAR, 2026)
Abstract: Sir Arthur Conan Doyle's Sherlock Holmes stories represent one of the most enduring and influential contributions to world literature. From the first novel published  in  1887  to  the  final  collections,  these  works  have  not  only  shaped  the development of the detective genre but have left a profound mark on modern culture as a whole. This article examines the defining characteristics of the Sherlock Holmes figure,  the  literary  techniques  employed  by  Doyle,  and  the  broader  socio-cultural significance of the canon. Particular attention is paid to Holmes's analytical intellect, his relationship with Dr. Watson, and the ways in which the stories reflect Victorian society. The study seeks to explain why the Holmes character has remained relevant for  over  135  years,  arguing  that  his  lasting  appeal  lies  in  the  combination  of extraordinary rationalism and deeply human contradiction.